1984
DOI: 10.1037/0278-7393.10.3.353
|View full text |Cite
|
Sign up to set email alerts
|

Orthographic and phonemic coding for lexical access: Evidence from Hebrew.

Abstract: In Hebrew script, vowels are represented by small dots appended to the consonants. However, in print the dots are almost always omitted, and because a single consonant string may represent several different words (with different vowels), the reader can assign to it a unique meaning and pronunciation only in relation to the syntactic and semantic contexts. We investigated the role of phonemic mediation for lexical access when printed Hebrew words are presented in isolation. Two experiments manipulated phonemic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
37
0

Year Published

1987
1987
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 8 publications
3
37
0
Order By: Relevance
“…Thus, there seems to be little doubt that to pronounce a common word in English requires processes that are not different from the processes required in reading common words in languages with a deeper orthography (Bentin, Bargai, & Katz, 1984;Dentin & Frost, 1987).…”
mentioning
confidence: 99%
“…Thus, there seems to be little doubt that to pronounce a common word in English requires processes that are not different from the processes required in reading common words in languages with a deeper orthography (Bentin, Bargai, & Katz, 1984;Dentin & Frost, 1987).…”
mentioning
confidence: 99%
“…These words have one rendition if construed as being written in Roman script and another when taken for Cyrillic; for example, POTOP in Roman means deluge, whereas in Cyrillic, it is pronounced /rotor/, meaning rotor. By contrast, for the more opaque (orthographically deep) Hebrew script, which typically omits vowels, thereby requiring more reliance on prior knowledge or context to infer the correct reading, Bentin, Bargai, and Katz (1984) found that Hebrew readers performed equally well on words with multiple phonological renditions, such as SPR (which may be read /sefer/ -book, /sapar/-barber, /saper/-tell, or /spor/-count; phonetic transcriptions taken from Bentin et al, 1984) and those with a single reading, such as KSF (/kesef/, meaning money). Further, Frost et al found that Hebrew readers were significantly faster at making lexical decisions as well as naming aloud words of high than of low frequency, whereas in Serbo-Croatian, both high and low frequency words elicited similar responses across tasks.…”
Section: Introductionmentioning
confidence: 99%
“…The implication here seems to be that in instances in which homographic and nonhomographic letter strings are processed as syntactically complex words, substantial resources are required for their morpho-syntactic decomposition. However, as shown by research conducted in Hebrew (Bentin et al 1984;Bentin and Frost 1987;Frost and Bentin 1992) as well as in IndoEuropean languages (Gottlob et al 1999;Hino et al 2002;Nievas and Mari-Beffa 2002;Pacht and Rayner 1993), in the case of heterophonic homographs, additional processing is required in order to disambiguate them prior to their morpho-syntactic decomposition, a requirement that further prolongs their processing.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, research conducted on Hebrew (Bentin et al 1984;Bentin and Frost 1987;Frost and Bentin 1992) as well as in Indo-European orthographies (Gottlob et al 1999;Hino et al 2002;Nievas and Mari-Beffa 2002;Pacht and Rayner 1993), indicates the processing of homographs to be significantly slower in comparison to nonhomographs. Such delays have been interpreted as reflecting time-consuming disambiguation processes the reader uses in order to suppress some of the automatically retrieved different word meanings.…”
Section: Introductionmentioning
confidence: 99%